Welke toekomst voor de Brusselse centrumwijken? - Mathieu Van Criekingen (Brussels Studies)
The accessibility of housing to low-income households in downtown Brussels has become much more complicated over the last decade. At the same time, there have been many clear signs of renewed investment in these neighbourhoods. This article proposes an interpretation of these ongoing changes in Brussels in terms of gentrification. The analysis is rooted in particular in a study of migratory statistics, that is to say, who is leaving the Brussels neighbourhoods that are becoming gentrified and where are they going (remaining in Brussels or leaving the city altogether)? Results indicate that, even if gentrification in Brussels is still marked by the gradual mutation of working-class areas into “trendy” rather than “chic” neighbourhoods, this process is already highly selective in social terms. Indeed, whilst various types of migrant are leaving the inner city, their destinations vary markedly, in line with their socio-economic profiles.